Subnasio-Sella Distance for Transnasal Approach to the Sella Region: Indirect vs. Direct Measurement on Sagittal Section of the Skull in Nigerians - Igwilo, Ihuoma A; Oremosu, Ademola A; Kanu, Okezie O; Dosumu, Olufunke (Asian Journal of Medical Sciences, 2013)
Objectives: The incidence of pituitary pathology requiring surgery is on the increase. The transnasal approach to anterior skull base is a technique which demands a thorough knowledge of the surgical anatomy. There is a dearth of knowledge on reference values for transnasal surgery on subjects of African descent. Thus the aim of this study is to ultimately improve visualisation of the surgical corridor, minimize surgical risks and improved maneuverability of surgical instruments during transnasal microsurgery (ergonomics). Methods & Materials: A total of 11 cadavers of Nigerian descent were employed in this study. Using the 3 piece caliper set (Big Horn Corporation®,India), an indirect measurement of the Subnasio-sella distance was obtained. Subsequently, a direct measurement was obtained from sagittal sections of the same skulls. Result: All randomly selected cadavers employed in the study were adult males of Sub-saharan descent. The mean indirect (distance from the anterior nasal spine i.e. subnasal point to the sella floor in an intact skull), direct A (subnasio-sella distance in a sagitally transected skull) and sella thickness measurements were found to be 8.6cm ± 0.38 cm, 8.7 cm ± 0.37 cm and 0.2 cm±0.05 cm respectively ,at 95% confidence interval. Comparison of the indirect and the direct A measurements showed statistical significance (p<0.5). A semi-logarithmic equation was derived: Direct A= 8.297 ln(Indirect measurement) – 9.079 Conclusion: Since transnasal transsphenoidal approach has been successfully used in the treatment of various anterior skull base pathologies, applying a relationship equation would guide choice of instruments employed and immensely minimize associated operative risks. DOI: http://dx.doi.org/10.3126/ajms.v5i2.8453 Asian Journal of Medical Science, Volume-5(2) 2014: 120-129